KEMAMPUAN MENULIS CERPEN SISWA KELAS VII SMPN 23 PEKANBARU - Rindi Santika Amri; M. Nur Mustafa; Abdul Razak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This Study discusses the ability to write short stories VII grade students of SMPN 23 Pekanbaru. This study was conducted to determine the level of ability to write short stories VII grade students of SMPN 23 Pekanbaru. This study used a test techniques to write short stories. To measure the level of students abilities can get analysis method by giving value to the aspect of the title, orientation, complications, and resolution on the short story. Based on research results of tehe study showed that the overall aspect of the level of ability to write short stories VII grade students of SMPN 23 Pekanbaru classified as moderate with the average is 71,84. If categorized the ability to write short stories in determining aspects of the title is high with the average is 84,84. Writing skills orientation is high with average is 84,09. The ability to write the complications classified as moderate with the average is 79,16, and the ability to write the resolution is moderate with average is 68,93.Keywords: The Ability To Write Short Stories VII Grade Students Of SMPN 23 Pekanbaru